Effectiveness of Periodontal Treatment to Improve Metabolic Control in Patients With Chronic Periodontitis and Type 2 Diabetes: A Meta‐Analysis of Randomized Clinical Trials. Issue 7 (1st July 2013) - Sgolastra, Fabrizio; Severino, Marco; Pietropaoli, Davide; Gatto, Roberto; Monaco, Annalisa
Abstract : Background: It was recently suggested that scaling and root planing (SRP) may help to improve glycemic and metabolic control in patients with chronic periodontitis (CP) and type 2 diabetes mellitus (DM2); however, the effectiveness of SRP in this role remains unclear. This meta‐analysis assesses the effectiveness of SRP in improving glycemic and metabolic control in patients with CP and DM2. Methods: A literature search of electronic databases was performed for articles published through May 16, 2012, followed by a manual search of several dental journals. A meta‐analysis was conducted according to the recommendations of the Cochrane Collaboration and the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). Weighted mean differences (MDs) and 95% confidence intervals (CIs) were calculated for glycated hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), total cholesterol (TC), triglycerides (TG), and high‐ and low‐density lipoprotein cholesterol (HDL and LDL, respectively). All outcomes were evaluated as changes from baseline to the end of follow‐up. Heterogeneity was assessed with the χ 2 ‐based Cochran Q test and I 2 statistic. The level of significance was set at P < 0.05. Results: After the study selection process, five randomized clinical trials were included. Results of the meta‐analysis indicated that SRP was effective in the reduction of HbA1c (MD = 0.65; 95% CI 0.43 to 0.88; P <0.05) and FPG (MD = 9.04; 95% CI 2.17 to 15.9; P <0.05), but no significant differences were found in the reduction of TC, TG, HDL, or LDL. No evidence of heterogeneity was detected. Conclusion: The meta‐analysis results seem to support the effectiveness of SRP in the improvement of glycemic control in patients with CP and DM2; however, future studies are needed to confirm these results.